2021
DOI: 10.3390/cells10051171
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Interference Against HIV-1 by Intrinsic Antiviral Factors: The Case of IFITMs

Abstract: HIV-1 is a complex retrovirus that is adapted to replicate in cells of the immune system. To do so, HIV-1, like other viruses, developed strategies to use several cellular processes to its advantage, but had also to come to terms with an arsenal of cellular innate defense proteins, or antiviral factors, that target more or less efficiently, virtually every step of the virus replicative cycle. Among antiviral restriction factors, the family of interferon-induced transmembrane proteins (IFITMs) has emerged as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…These factors act against a broad spectrum of viruses, mostly enveloped, including IAV and West Nile virus (WNV) [94,95]. Over the past 10 years, IFITMs have also emerged as HIV-1 inhibitors, interfering with both early and late viral replication steps thanks to their ability to control cellular and viral membrane fusion [69,96]. Recently, it has been also reported that overexpression of IFITMs restricts β-coronavirus SARS-CoV-2 infection, supporting results previously obtained upon human coronavirus OC43 infection [70,97,98].…”
Section: Ifitm Proteinsmentioning
confidence: 99%
“…These factors act against a broad spectrum of viruses, mostly enveloped, including IAV and West Nile virus (WNV) [94,95]. Over the past 10 years, IFITMs have also emerged as HIV-1 inhibitors, interfering with both early and late viral replication steps thanks to their ability to control cellular and viral membrane fusion [69,96]. Recently, it has been also reported that overexpression of IFITMs restricts β-coronavirus SARS-CoV-2 infection, supporting results previously obtained upon human coronavirus OC43 infection [70,97,98].…”
Section: Ifitm Proteinsmentioning
confidence: 99%
“…Interferon-inducible transmembrane (IFITM) proteins are a family of small transmembrane proteins that localize in the plasma and endolysosomal membranes and inhibit viral infections by impeding virus entry and reducing the production of infectious virions ( Yánez et al., 2020 ; Marziali and Cimarelli, 2021 ; Majdoul and Compton, 2022 ). Among them, IFITM3 is a conserved cellular transmembrane protein (133 amino acids) which resides in late endosomes and lysosomes and inhibits fusion of various enveloped viruses by blocking formation of fusion pores at the post-hemifusion stage ( Coomer et al., 2021 ; Majdoul and Compton, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the cellular components that play negative effects on virus replication are effectors of type I interferon responses (IFN-I), or interferon-sensitive genes (ISGs) [1]. While as part of a whole they participate to a generalized anti-pathogen state, individual ISGs can be either specific for one class of viruses, or can inhibit processes common to very diverse viruses, as for example the doublestranded RNA-activated protein kinase R (PKR), or the interferon-induced transmembrane proteins (IFITMs) that inhibits virus-to-cell membrane fusion [2][3][4][5][6]. In recent years, the search for cellular effectors directed against the HIV-1 retrovirus has drawn particular interest, spurring a number of genetic screens that are defining the complex cellular landscape in which HIV replication occurs (for example [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%